Emotional Contagion: Research on the Influencing Factors of Social Media Users' Negative Emotional Communication During the COVID-19 Pandemic - Lu, Dan; Hong, Dian (Frontiers in Psychology, 2022)
During the epidemic, social media platforms were frequently used by users to express and spread negative emotions. Under emotional contagion, individual emotions gradually generalized into group emotions. At the same time, the public could not regulate their emotions and lack access to release them rationally. The study explores the factors influencing the negative emotions communication among social media users during the COVID-19 epidemic from the perspective of emotion contagion theory to discover the psychological mechanisms among the public.The questionnaire was tested for reliability and validity and then distributed online on Chinese social media platforms, and the data collected were statistically analyzed.The findings show that there are significant differences in negative emotion communication in social media among different age groups; the seven dimensions of deindividuation, risk perception, group identity, group efficacy, event stimulation, event publicness, and emotion contagion all have significant positive effects on users' negative emotion communication.The study aims to raise public awareness of negative emotions and promote the reconstruction and recovery of public mental health in the epidemic era.